La chanson française, un art de métèques ? - Yves Borowice (Amnis)
What can teach us an art as popular as chanson on the history, the memory and the imagination of immigration? The first part of the article is devoted to a broad inventory of the “foreign contribution” in this artistic field, whose cultural importance and social impact are considerable. Based on many examples, it insists on the seniority of the phenomenon, which goes back up to the end of theninetheenth century and remains today. All the actors of the professional environment — not only the singers — are taken into account. The extreme diversity of courses and routes is approached, as well as the conceptual and terminological questions which result from it. A geography of the origins is eventually sketched. The second part of the article will examine the historical and aesthetic conclusions that can be drawn from this impressive melting pot.